(untitled) (Research, Society and Development, 2022)
The National High School Exam (ENEM) is one of the main assessments of Brazilian Basic Education, as the data obtained by its application influence the elaboration of public policies and classroom practice. However, one of the main challenges of ENEM is to be an accessible assessment tool for different audiences in Brazil, taking into account social, economic, regional and accessibility factors. Thus, the objective of this work is to know the performance microdata of the Northeast region of the Mathematics area and its ENEM technologies, in the years 2017 to 2019, and to draw reflections on how social factors influence the performance of students in this area. Thus, initially a bibliographic research was carried out in order to know the Exam, its application and how it guides public policies for High School and Higher Education. Subsequently, a documentary research was carried out on the microdata of performance in the area of Mathematics in the years 2017 to 2019, in order to analyze the influence of social factors on the performance of Mathematics of participants in the Northeast region. In the last stage of the research, we describe the results and observations on the analyzed data. It is noticed that socioeconomic factors, family structures and school influence the mathematics performance of ENEM participants and that it is necessary to know their social context, as it will enable the elaboration of public actions and policies in the educational field, in order to provide equal conditions for all participants.